A New Model of Genetic Zone Routing Protocol (GZRP): The Process of Load Balancing and Offloading on The UMTS-IEEE 802.11g Hybrid Networks - Setiyo Budiyanto; Arissetyanto Nugroho (Universitas Ahmad Dahlan, 2017)
The stages of the process of Genetic Algorithm (GA), are: Encoding Genotype and Chromosome; Set Initialization Population; Evaluation Fitness Function; and Selection Process as well as in the later stages Cross Over Process and Mutation. Outputs from the tests performed in this study can be obtained by comparing the Genes of the